Cloud infrastructure of INP'S Astana branch - PE "NULITS" and its integration with distributed JINR cloud infrastructure - Mazhitova, Yelena; Balashov, Nikita; Aleksandr, Baranov; Kutovskiy, Nikolay; Semenov, Roman; Potapchuk, Boris (XXII INTERNATIONAL SCIENTIFIC CONFERENCE OF YOUNG SCIENTISTS AND SPECIALISTS (AYSS-2018), 2019)
The article describes the Institute of Nuclear Physics’ (INP) Astana branch - private establishments “Nazarbayev University Library and IT services” (PE NULITS) cloud and its integration with the distributed cloud infrastructure consisting of the Laboratory of Information Technologies of the Joint Institute for Nuclear Research (JINR) cloud as well as clouds of some JINR Member State organizations. It explains a motivation of that work, an approach it is based on, working plan of the integration.
Keywords: Institute of Nuclear Physics; Nazarbayev University Library and IT services; JINR cloud infrastructure